An unusual reaction of a Reissert compound involving alkylation, rearrangement, SNAr and SET processes. Issue 11 (14th March 2018) - Gibson, Harry W.; Niu, Zhenbin; Lee, Minjae; Price, Terry L.; Schoonover, Daniel V.; Berg, Michael A.G.
Graphical abstract: Highlights: Reaction of Reissert compound1 via its anion with "stabilized" i- PrI yields four products. The expected isopropyl compound2 is isolated in 55% yield at 0 °C. The expected rearrangement product, ketone3, is isolated in low yield. Cyano lactam4 is the main product at 22 °C via from SN Ar cyclization of the anion. Isopropyl lactam5 is a minor product. It results from an SET process involving4 . Abstract: Reaction of isoquinoline Reissert compound1 with NaH and then isopropyl iodide in DMF at 22 °C led to four isolated products. Ketone3 is the expected product of the well-known rearrangement of the intermediate Reissert anion. Cyano lactam4 results from SN Ar intramolecular displacement of the fluoride ion from the activated aroyl moiety of the anion. Isopropyl lactam5 is proposed to result from a SET (single electron transfer) process via formation of the radical anion of4, subsequent loss of the cyanide ion, and coupling of the resultant radical with isopropyl radicals formed via copper used to "stabilize" the alkyl iodide. The expected alkylated product2 is also formed via a SET process involving electron transfer from the Reissert anion to4, leading to the Reissert radical. Use of "non-stabilized" bromide or iodide led to3 and4, but did not produce2 or5 .